Images of women in the A-level literature taught in Tanzanian secondary schools and their implications for development : a thesis presented in partial fulfilment of the requirements for the degree of Master of Phiilosophy in Development Studies at Massey University, Palmerston North, New Zealand / - Allardice, Elizabeth (Massey University, 2000)
Traditionally in Tanzania gendered education was carried out by family members and 'elders', with the purpose of equipping young people with the skills and knowledge they would need to play a complete role in their society. Contact with Arab traders led to the adoption of Islam in some communities and the establishment of Koranic schools. With Christianity and the colonial administration; first by Germany and later by Britain, came Western formal education. Women had little access to either of these forms of education however and were not admitted in large numbers to schools until the socialist education policies of the post independence government were put into place. Despite these policies, society's discriminatory attitudes towards women continued to mitigate women's advancement to higher education. This has helped to lead to women's low status in society, the lack of recognition for their contributions to that society and their inability to shape the development of Tanzania on an equal basis with men. Within the education system women and girls suffer many disadvantages which contribute to their lack of academic success. Not least of these is a biased curriculum which is particularly evident in the content of school text books and reading material. Books in the A level literature in English syllabus are all written by men and an analysis of the content of the eight most frequently used books shows the predominance of negative images of women and gender relations which denigrate and devalue women and girls. These negative images, internalised by the female students, prevent them achieving the goals of the syllabus and may contribute to low self esteem and their subsequent low representation in tertiary institutions. Books written by African women writers, which portray more positive images of women and alternative gender relations, are available and would be valuable additions to the syllabus for both male and female students.
Keywords: Tanzania; Literature -- Study and teaching (Secondary); Women in literature; Sex role in literature; Sex discrimination in education; Women -- Education